A motivação de licenciandos em música sob a perspectiva da teoria da autodeterminação - Araújo, Isac Rufino de (2015)
This research had as main aim to verify the motivational quality of music students at four public universities in the Northeast of Brazil, based on the Self-Determination Theory (SDT). This perspective was proposed by Edward Deci and Richard Ryan (1985, 2000, 2008a, 2008b), and considers the qualitative aspects of motivation. It defends that the individuals have a natural tendency to self-regulation; it adopts the concept of internalizations through a continuum of self-determination conceived in the mini-theory of organismic integration. The research presents a descriptive, exploratory and correlational approach. To collect data, it was submitted a self-report questionnaire, based on the Academic Motivational Scale, translated and validated by Guimarães and Bzuneck (2008), which allow us to verify the motivation types according to a selfdeterminational continuum. According to this application, the instrument has shown evidence of satisfactory validity, with a good internal consistence and correlations from weak to moderate scale. The obtained data were collected from 380 music students, analyzed through a descriptive and inferential statistics, considering a few procedures: frequencies, averages, standard deviation, factorial analysis, internal consistence analysis through Cronbach Alpha, Pearson’s correlational analysis and variance analysis. The analyzed data show that high averages in the evaluation of self-determined motivation and low evaluation in demotivation and less autonomy motivation. Many students revealed strong intention to conclude the course. It was identified less autonomous motivation and more motivation among the students with intention to work in other areas, some of them concluded the final training process in Music Course, and say that they are in this course because they had no other option. We conclude that those graduated in Music Course, represented in this sample, show a good motivational quality. But after a few time there is a tendency in decreasing autonomous motivation because of some requirements of an academic course. In this sense, the courses must create strategies to maintain a self-determined behavior so that students can realize their autonomous motivation, identifying its importance, value and meaning along the Course.